2020
DOI: 10.1016/j.cmet.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Is Associated with Higher Incidence of Acidosis, but Not Mortality, in Individuals with COVID-19 and Pre-existing Type 2 Diabetes

Abstract: Summary The safety and efficacy of anti-diabetic drugs are critical for maximizing the beneficial impacts of well-controlled blood glucose on the prognosis of individuals with COVID-19 and pre-existing type 2 diabetes (T2D). Metformin is the most commonly prescribed first-line medication for T2D, but its impact on the outcomes of individuals with COVID-19 and T2D remains to be clarified. Our current retrospective study in a cohort of 1,213 hospitalized individuals with COVID-19 and pre-existing T2D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
170
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(177 citation statements)
references
References 48 publications
4
170
0
3
Order By: Relevance
“…In contrast, some studies did not report such an association between metformin treatment and improved COVID-related outcomes in patients with type 2 diabetes. One retrospective observational study form China including 1213 patients with T2D hospitalised for COVID-19 (678 metformin users) found a neutral effect of metformin on 28-day mortality [32] . Another retrospective study from Korea, which was based on claims data, found no definite association between metformin use and COVID-19 outcomes [33] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some studies did not report such an association between metformin treatment and improved COVID-related outcomes in patients with type 2 diabetes. One retrospective observational study form China including 1213 patients with T2D hospitalised for COVID-19 (678 metformin users) found a neutral effect of metformin on 28-day mortality [32] . Another retrospective study from Korea, which was based on claims data, found no definite association between metformin use and COVID-19 outcomes [33] .…”
Section: Discussionmentioning
confidence: 99%
“…A part of the baseline data in this manuscript have been used in our previous articles. 30 , 31 , 32 , 33 …”
Section: Methodsmentioning
confidence: 99%
“…Although the analysis excluded individuals with contraindications for taking metformin, metabolic acidosis, including lactic acidosis, was more common in metformin-treated subjects, notably in people with clinically severe COVID-19 illness. Acidosis was more common in subjects with hypoxemia, higher metformin doses (2–3 g daily), and an estimated glomerular filtration rate (eGFR) < 60 ( Cheng et al., 2020 ); however, all-cause mortality determined at day 28 of hospitalization was not different between groups.…”
Section: Glucose-lowering Therapies and Covid-19 Outcomesmentioning
confidence: 99%
“…Cheng and colleagues retrospectively analyzed outcomes in 678 metformin- versus 535 non-metformin-treated Chinese subjects, selected from among 2,563 people hospitalized with pre-existing T2D and COVID-19, after excluding 1,350 people from the analysis, for reasons including the exclusive use of insulin or no record of using glucose-lowering medications ( Cheng et al., 2020 ). Although the analysis excluded individuals with contraindications for taking metformin, metabolic acidosis, including lactic acidosis, was more common in metformin-treated subjects, notably in people with clinically severe COVID-19 illness.…”
Section: Glucose-lowering Therapies and Covid-19 Outcomesmentioning
confidence: 99%